Design and Development of Online Collaborative Learning Platform of Kit-Build Concept Map - Pinandito, Aryo; Prasetya, Didik Dwi; Az-zahra, Hanifah Muslimah; Wardhono, Wibisono Sukmo; Hayashi, Yusuke; Hirashima, Tsukasa (Journal of Information Technology and Computer Science, 2021)
A concept map is deemed a useful teaching and learning tool. It offers many potential advantages over just representing the students’ knowledge and understanding during learning, and have been widely used to support learning. Kit-Build concept map is one learning framework that incorporate digital concept map for its learning activities. Learning with Kit-Build concept map has been found to have better learning effects towards students' understanding and knowledge retention. Incorporating Kit-Build concept map into collaborative learning have been reported to have better outcome than the traditional collaborative learning. However, collaborative learning with Kit-Build concept map cannot be accomodated with the current Kit-Build system where learning activity is conducted online. This study presents the design and development of online collaborative learning platform of Kit-Build Concept Map. A prototype of the collaboration system to support collaborative learning with Kit-Build concept map is developed and be evaluated to portray its potential usability for further development and practical use. The result suggested that incorporating Socket.IO as a real-time communication middleware is effective to deliver online collaborative learning features into the Kit-Build system. Preliminary evaluation to the system also suggested that the system has the potential for actual use in supporting distant collaborative learning with Kit-Build concept map.